2020
DOI: 10.1007/s00345-020-03078-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative antithrombotic (antiplatelet and anticoagulant) therapy in urological practice: a critical assessment and summary of the clinical practice guidelines

Abstract: Purpose:The perioperative management of patients who are receiving antithrombotic (antiplatelet or anticoagulant) therapy and require urologic surgery is challenging due to the inherent risk for surgical bleeding and the need to minimize thromboembolic risk. The aim of this review is to assess the quality and consistency of clinical practice guidelines (CPGs) and clinical practice recommendations (CPRs) on this topic, and to summarize the evidence and associated strength of recommendations relating to perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In these cases, long-term stable and uninterrupted monitoring is required. Long-term stable monitoring is also needed to prevent the irreversible trauma caused by sudden outbreaks to the human body [ 18 , 19 ]. If long-term monitoring of the abovementioned patients can be achieved, it will not only dig out the deep-seated pathology of the patients to facilitate targeted treatment, but, at the same time, it is also very helpful for urgent treatment of diseases, because actually the best treatment period for these diseases is at the beginning of the outbreak.…”
Section: Cardiovascular Disease and Antithrombotic And Anticoagulant Treatmentmentioning
confidence: 99%
“…In these cases, long-term stable and uninterrupted monitoring is required. Long-term stable monitoring is also needed to prevent the irreversible trauma caused by sudden outbreaks to the human body [ 18 , 19 ]. If long-term monitoring of the abovementioned patients can be achieved, it will not only dig out the deep-seated pathology of the patients to facilitate targeted treatment, but, at the same time, it is also very helpful for urgent treatment of diseases, because actually the best treatment period for these diseases is at the beginning of the outbreak.…”
Section: Cardiovascular Disease and Antithrombotic And Anticoagulant Treatmentmentioning
confidence: 99%
“…The European Association of Urology (EAU) recommends that the timing of preoperative discontinuation of antithrombotic drugs in non-extremely high-risk patients should be adjusted according to the type of antithrombotic drug, ranging from 12 h before surgery (e.g., for unfractionated heparin) to 5–7 days (e.g., for clopidogrel) [ 25 ]. Dimitropoulos K et al [ 12 ] suggested that oral antithrombotic therapy should be discontinued 7–10 days before TURP in patients with low risk of cardiovascular events. There is relatively much literature in this field regarding the effect of preoperative discontinuation of antithrombotic drugs on postoperative bleeding after TURP [ 14 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The timing of preoperative discontinuation of antithrombotic drugs is critical. However, the existing studies [ 11 , 12 ] mostly focus on the influence of stopping time on postoperative hemorrhage risk and fail to comprehensively assess the risk of hemorrhage and VTE. In addition, most studies [ 13 , 14 , 15 ] only analyzed the effect of aspirin on TURP surgery, which is difficult to fully adapt to the actual complex clinical situation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a comprehensive literature search was performed. Compared with another recent paper addressing perioperative antithrombotic therapy in urological practice, 26 we had the following distinctions. First, we attempted to collect all information related to the guideline development process through carefully reading guideline documents, appendices and methodological manuals, and we included ten CPGs addressing the perioperative management of DAPT in patients with coronary stents who needed elective noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%